The Electrodeposition of Nickel Coatings, Modified Ultrafine Diamonds - Zabludovsky, V.A.; Tytarenko , V.V. (Physics and Chemistry of Solid State, 2016)
The polarization analysis of nickelwhen the concentration of ultrafine particles of diamond (UFD) in the electrolyte solution and its frequency mixing. It was found that the addition of nanodiamond particles in an aqueous electrolyte solution causes a shift reduction potential nickel electronegative region, increase resistance to charge transfer and the formation of a fine-grained, close-packed surfaces that determined the increase of microhardness and wear resistance of the metal coating.